Managing the transition period of dairy cows to prevent major metabolic postpartum disorders - BROZOS, C. N.; KALAITZAKIS, E.; PANOUSIS, N. (Journal of the Hellenic Veterinary Medical Society, 2017)
The transition period refers to the time between 3-4 weeks prior to and 4 weeks after calving. This is the period with the highest incidence of metabolic and other periparturient disorders. Many of these disorders interrelated and often coincide. Proper management and nutrition of the transition cow are critical for obtaining maximum dry matter intake, good health, increased reproductive efficiency and optimum milk production in the following lactation. The present review is comprised from two parts. In the first one, selected information is provided concerning the most important metabolic diseases of the transition period (hypocalcemia, ketosis) and, in brief, how hypocalcemia is interrelated to other diseases (mastitis, metritis, retained fetal membranes and abomasal displacement). In the second part, up-to-date nutritional methods applied in the transition period to prevent these metabolic periparturient diseases, with emphasis in hypocalcemia, are described.